Historical awareness of social science teachers in Albay community colleges - Briones, John Henry (Humanities, Arts and Social Sciences Studies, 2025)
This study focused on the level of awareness of Social Science teachers in Albay community colleges. It addresses the following questions: 1) to determine the level of awareness of the faculty on historical distortion and historical fact, and 2) to propose training that could enhance the participants historical awareness. A descriptive mixed-method design was utilized along with a survey questionnaire, document review, and interview guide as a tool for data collection. The study participants were Social Science faculty teaching Readings in Philippine History in Albay community colleges. The frequency, weighted mean, and rank were used to interpret and quantify the collected data. The results showed that Social Science teachers were moderately aware of historical distortion. In addition, there is a consensus made by teachers that historical distortions are unacceptable and cannot be tolerated. Consequently, the teachers believed that this illegitimate practice of revisionism required a careful strategy to counter the threat it posed to the nation’s moral fabric and consciousness. Concerning facts, the Social Science teachers demonstrated a high level of awareness, which signifies that they could identify the listed items as factual because they were part of their basic knowledge of history. Reasons and factors are provided to substantiate how Social Science teachers distinguish between historical distortions and facts. Moreover, training/workshops/symposia on the challenges faced by Philippine history is the preferred proposed training by the participants. Hence, historical awareness and training play an imperative role in confronting a pressing issue in the study of history: historical distortion.